CARABELLI TRAIT AND SHOVEL SHAPED INCISORS AMONG NEWARI CHILDREN OF BHAKTAPUR - Pradhan, Megha; Joshi, Ujjwal; Chaulagain, Rajib; Poudyal, Sijan (Journal of Chitwan Medical College, 2024)
Background: Carabelli’s trait can be useful in establishing phylogenic relationships between closely related populations. Most of the studies have reported only on permanent maxillary first molar for the Carabelli trait. Studies on the Carabelli trait have been very limited. This study aimed to assess two selected morphometric traits in Newari Children in Bhaktapur. Methods: This cross-sectional study was conducted among 6-14year old 340 children belonging to the Newar community of Bhaktapur after obtaining the required consent and assent form. Children who had healthy primary second molars and/or permanent first molars were included while severely carious or restored teeth, undergoing orthodontic treatment, having traumatic injuries to teeth, special health care needs, developmental anomalies, attrited cusps and having non‑eruption/partial eruption of the desired tooth unilaterally/bilaterally were excluded. Data was collected, and statistical analysis was done. The study was analyzed using the measure of central tendency and measure of dispersion with SPSS software version 16. Results: The most prominent shovelling trait found in the maxillary central incisor was trace among 41.8% of participants. Cusp of the Carabelli trait was seen in 49.1% in right and 45.6% in left maxillary permanent molars of participants, and small vertical ridge and groove was the most prominent trait among the Carabelli trait of both primary and permanent molars. Conclusions: Non-metric dental traits can be evaluated for identification of ethnic groups and for clinical management in various dental procedures.